THE AUTHENTIC ASSESSMENT IN IMPLEMENTATION INDEPENDENT CURRICULUM AS BEST PRACTICE WORKSHOP QUIZIZZ FOR TEACHERS AT ELEMENTARY SCHOOL - Indri Pudjiati; Faisal Madani (Universitas Majalengka, 2024)
The problems after the COVID-19 pandemic regarding learning loss and gaps in teaching and learning activities carried out by teachers on students are related to technological adaptation, where teachers need to build learning communities in self-development. This research is motivated by self-development activities for educators, especially teachers, to build various learning communities with a common vision for student-centered learning. This study aims to describe the authentic assessment in the implementation of The Independent curriculum as a good practice in the form of a Quizizz workshop for elementary school teachers in the District Citeureup Bogor regency. The research method used is descriptive qualitative research, with a phenomenological approach. Phenomenological observed in this study in the form of activities sharing good practices Quizizz workshop as the implementation of an independent curriculum for elementary school teachers conducted face-to-face/offline in target schools. Data collection techniques are observation and interview. The source of data in this study came from primary data in the form of interviews and secondary data in the form of good practice documents from the Quizizz workshop. Based on the implementation of good practices that have been done, it can be concluded: 1) this activity has been able to improve teacher performance and understanding of the implementation of The Independent curriculum; 2) foster positive awareness and increase teacher knowledge of the skills to prepare authentic assessments assisted by the Quizizz application as an implementation of The Independent curriculum; 3) encourage teacher awareness in sharing good learning practices that build learning communities for elementary school teachers. The results showed that the Quizizz workshop can be a good practice to facilitate teachers in conducting authentic assessments.